Knowledge Sharing in Small and Medium Enterprises: A PLS-SEM Analysis of Employee Engagement, Innovation Capability and Organizational Performance - Amankwah, Godfred; Atigah, Nathan Awelama; Attoh, Alfred; Amankwah, Kennedy (Organizations and Markets in Emerging Economies, 2026)
The paper examines knowledge sharing roles as factors in organizational performance in Ghana. Consequently, employee engagement and innovation capability are intervening variables in the knowledge sharing–performance relationship. The study employed a PLS-SEM approach to examine data from 347 managers in Ghana’s SME sector. The results showed that knowledge sharing directly improves organizational performance in the emerging economy. Both employee engagement and innovation capability significantly mediate the relationship between knowledge sharing and performance. Knowledge sharing from its end positively impacted employee engagement and innovation capability outcomes. These mediating variables, in turn, contributed to the performance of organizations under review in the SME category. Through the dual mediation mechanism, knowledge sharing effectively creates organizational value. Henceforth, increased employee engagement and innovation capacity become essential pathways towards performance enhancement. The firm’s particular style of knowledge sharing, both tacit and explicit, is translated into performance outcomes through these intangible assets. These results will help immensely in designing a feasible knowledge management strategy in two resource-constrained milieus, where employee engagement and innovation capacity matter for transforming knowledge assets into organizational performance outcomes. The study contributes to the knowledge management literature by establishing dual pathways of mediation. It also offers SME managers practical implications to gain a competitive advantage in knowledge resources.